Immigration-Related Document Fraud : Overview of Civil, Criminal, and Immigration Consequences. (U.S. Congressional Research., 2006)
Discusses civil and criminal penalties for immigration-related document fraud under the Immigration and Nationality Act, including forgery, misuse, and/or misrepresentation on visas and other immigration-related documents, and false statements relating to naturalization, citizenship, or alien registry. Outlines consequences of such fraud upon admission, removal, and eligibility for immigration-related benefits.